Building Business Sustainability: The Role Of Islamic Financial Literacy And Basic Accounting Understanding - Nuril Badria; Naimatul Hasanah (Journal of Islamic Economics, 2025)
This study aims to determine the effect of Islamic financial literacy and basic accounting understanding on business sustainability at Madura grocery stores in Malang City. Business sustainability is a crucial aspect in maintaining the existence of MSMEs, especially in facing economic challenges and market dynamics. Islamic financial literacy reflects a business owner's understanding of Sharia principles in financial management, while basic accounting understanding reflects the ability to systematically record, manage, and evaluate a business's financial information. This study used a quantitative approach with a sample of 136 respondents who were owners or managers of 24-hour Madura grocery stores in Malang City. Data analysis was conducted using multiple linear regression. The results indicate that, both simultaneously and partially, Islamic financial literacy and basic accounting understanding significantly influence business sustainability. This finding indicates the importance of improving Sharia-based financial education and providing simple accounting training for MSMEs to support business sustainability.